INNOVATION AS A FACTOR OF ENTREPRENEURSHIP DEVELOPMENT WITH A SPECIAL FOCUS ON ISRAEL AND DISRUPTIVE INNOVATIONS - Ljubičić, Ivana (Ekonomija - teorija i praksa, 2022)
The subject of this paper are innovations, which play a crucial role in the development of entrepreneurship in the modern world. Sometimes it is enough for a company to make some important or even incremental innovation and to gain a market and competitive advantage. But sometimes, as in the case of the Finnish mobile phone manufacturer - Nokia, it is enough not to respond quickly enough before the emergence of a disruptive innovation and to lose 92% of the market as a result. Companies that have an environmental change rate faster than the rate of change of the company itself, i.e., those that implement innovations more slowly than the environment changes, are first doomed to lag behind others, and then also to become marginalized and eventually to disappear and be completely shut down. The importance of this paper is the innovation factor which remains paramount to the advancement of entrepreneurship, and whether it will be executed and driven in one way or another, by a government incentive or by the booming private sector, is irrelevant after all. China does this by direct government investment in innovation and innovative technologies, while in the US and to a lesser extent in Israel, it is happening in the free market. The countries of Scandinavia, Switzerland, Japan, South Korea and Singapore, as well as the “start-up nation”, Israel, have a direct proportion of their GDP per capita and innovation index. This all tells us how important it is to support innovation. The induction, deduction, analysis, synthesis and, above all, desk research methods have been used for producing this paper.